2011
DOI: 10.1159/000335560
|View full text |Cite
|
Sign up to set email alerts
|

Topical Imiquimod 5% Cream for Pediatric Plaque Morphea: A Prospective, Multiple-Baseline, Open-Label Pilot Study

Abstract: Background/Aims: Therapeutic options for the treatment of plaque morphea are limited. We explored the efficacy and safety of imiquimod cream in children with plaque morphea. Methods: Prospective, open-label, double-baseline study, using imiquimod 5% cream topically for 9 months. The primary outcome measure was improvement in the thickening of morphea plaques using a visual analog scale (VAS) and the DIET score (dyspigmentation/induration/erythema/telangiectasia). Secondary outcome measures were clinicoradiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 48 publications
1
29
0
3
Order By: Relevance
“…Multiple options exist and are commonly used when treating mild morphea in children, but few of these options are based on evidence. The existing studies involve the use of such topical immunomodulators as tacrolimus, imiquimod, and calcipotriene, of which our study population commonly chose tacrolimus and calcipotriene, but the small sample size and often the lack of a control group limited these studies . Topical corticosteroids, the form of topical medication that dermatologists use most commonly for pediatric morphea, have never been studied in the treatment of pediatric morphea .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple options exist and are commonly used when treating mild morphea in children, but few of these options are based on evidence. The existing studies involve the use of such topical immunomodulators as tacrolimus, imiquimod, and calcipotriene, of which our study population commonly chose tacrolimus and calcipotriene, but the small sample size and often the lack of a control group limited these studies . Topical corticosteroids, the form of topical medication that dermatologists use most commonly for pediatric morphea, have never been studied in the treatment of pediatric morphea .…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of clinicians in the United Kingdom reported that topical corticosteroids are the most commonly used medication to treat plaque morphea, but no evidence was provided regarding their use . Topical immune modulators, including calcineurin inhibitors, calcipotriene, and imiquimod, are often used but have been evaluated only in small studies without the use of a control group . Lack of consensus on objective outcome measures also limits studies.…”
Section: Introductionmentioning
confidence: 99%
“…36 So far, studies on pimecrolimus for LS are missing. The topical immune response modifier imiquimod has been reported to significantly improve abnormal pigmentation, sclerosis and erythema in LS [37][38][39] but cannot be recommended for LS until more valid data are available. Intralesional interferon gamma did not prove effective in LS in a double-blinded, placebo-controlled trial.…”
Section: Treatmentmentioning
confidence: 99%
“…49,50 Treatment with twice-daily topical tacrolimus is supported by a randomized placebo-controlled trial. 52 Additional topical therapies that have shown benefit in prospective studies include topical imiquimod applied three to five times per week, 53,54 combination calcipotriol and betamethasone dipropionate applied once to twice daily, 55 and calcipotriene applied and occluded twice daily. 56 Topical steroids, anecdotally the most commonly used therapy for plaque morphea, may be effective, but to date there are no data supporting their efficacy as a solitary agent.…”
Section: Prognosismentioning
confidence: 99%